URGENSI KRIMINALISASI TERHADAP PENIKMAT JASA PROSTITUSI ONLINE DALAM HUKUM PIDANA INDONESIA - Yudith Muhammad; Emilda Firdaus; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Online prostitution is an activity of prostitution or an activity that makes a person an object to be traded via electronic or online media, the media used such as michat, whatsapp, and telegram. In other words, here the community is demanded to be more able to respect the norms and values contained in people's lives because this online prostitution case can destroy the future of the nation, such as cases that were found with perpetrators who were still teenagers and the lack of strict legislation to ensnare them. prostitute.In writing this thesis, the author uses the synchronization level normative research method, namely a study of secondary data in the form of laws and regulations, as well as the results of research by law scholars, such as books related to the subject matter of which then proceed with research on primary data (data obtained directly from respondents). To draw conclusions from the data collected, the authors use deductive analysis techniques, namely by drawing conclusions from general to specific conclusions.From the results of the research on the problem, there are two things that can be concluded. Law enforcement against users of online prostitution services, in Indonesia there are various laws and regulations that prohibit prostitution, but these rules are not yet comprehensive to ensnare the parties involved, especially users of prostitution services. Secondly, criminal law policies that are in accordance with the needs of the community are one of the ways to overcome prostitution in Indonesia, the application of such criminal law policies does not harm either party, there is injustice in ensnaring the practice of prostitution, therefore a sense of justice is applied in ensnaring The perpetrators of prostitution will be realized if the criminal law policy is changed and replaced with a new one so that the perpetrator and the user of prostitution can be subject to legal traps through statutory instruments.Keywords: Criminalization, Prostitution, Prostitution Consumers